2018
DOI: 10.3390/sports6020030
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Linear Speed and Lower-Body Power with Change-of-Direction Speed in National Collegiate Athletic Association Divisions I and II Women Soccer Athletes

Abstract: This study investigated relationships that linear speed and lower-body power have on change-of-direction (COD) speed in collegiate women soccer players. Data from two Division I (n = 39) and one Division II (n = 18) schools were analyzed. Subjects were assessed in: power (vertical jump (VJ); jump height, peak anaerobic power measured in watts (PAPw), power-to-body mass ratio (P:BM); linear speed (10-m sprint); and COD speed (modified T-test (MTT), 505, COD deficit). Independent samples T-tests derived signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
68
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(89 citation statements)
references
References 41 publications
(114 reference statements)
12
68
5
Order By: Relevance
“…Bearing in mind the age span of the Journal of Human Kinetics -volume 72/2020 http://www.johk.pl groups of our study, and despite the important variations in body dimensions, no significant effect of body height was detected, in contrast to Chaouachi et al (2012): body mass had significant effects (p < 0.05) for MATtop and MATfree, but not for the T-Test in Tunisian National Soccer League 1. Interestingly, while the CMJ and a quintuple horizontal jump test did not contribute to the T-Test performance for senior soccer players (Chaouachi et al, 2012), and no significant regreession equation could be found for NCAA woman Division I and II soccer players on the MATtop after considering, among others, vertical jumping as a factor (Lockie et al, 2018), the explanatory jumping factor varied from MATfree to MATtop in this study. That is, the primacy of a more open drill (i.e., ACMJ) for the freedisplacement test and a closer drill (i.e., CMJ) for the constrained-displacement test can indicate the existence of slightly different CODA profiles, as far as lower limbs are concerned.…”
Section: Discussioncontrasting
confidence: 62%
“…Bearing in mind the age span of the Journal of Human Kinetics -volume 72/2020 http://www.johk.pl groups of our study, and despite the important variations in body dimensions, no significant effect of body height was detected, in contrast to Chaouachi et al (2012): body mass had significant effects (p < 0.05) for MATtop and MATfree, but not for the T-Test in Tunisian National Soccer League 1. Interestingly, while the CMJ and a quintuple horizontal jump test did not contribute to the T-Test performance for senior soccer players (Chaouachi et al, 2012), and no significant regreession equation could be found for NCAA woman Division I and II soccer players on the MATtop after considering, among others, vertical jumping as a factor (Lockie et al, 2018), the explanatory jumping factor varied from MATfree to MATtop in this study. That is, the primacy of a more open drill (i.e., ACMJ) for the freedisplacement test and a closer drill (i.e., CMJ) for the constrained-displacement test can indicate the existence of slightly different CODA profiles, as far as lower limbs are concerned.…”
Section: Discussioncontrasting
confidence: 62%
“…These data are supported by previous research where the greatest improvements in COD agility, indicated by 18.3-meter shuttle sprint, were noted to occur in the first year of training across all positional groups (Stodden & Galitski, 2010). Previous research has indicated that increases in concentric, eccentric, and isometric strength are all strong factors in improving COD ability (Lockie, Dawes, & Jones, 2018;Hammami et al, 2018;Suchomel, Nimphius, & Stone, 2017;Spiteri et al, 2013;Spiteri et al, 2014). A greater eccentric strength capacity improves the breaking force (Spiteri et al, 2014), thus the ability to accept and apply force during this phase is enhanced.…”
Section: Discussionsupporting
confidence: 85%
“…To the best of our knowledge, this is the first study to compare COD deficit and 505 performance across a range of team-sports, while considering the effect of sex and sport. The COD deficits presented for the team-sports in Table 1 and Table 2 are in line with those reported in male cricket (D: 0.617 ± 0073 s, ND: 0.670 ± 0.087 s) [6], female rugby (left: 0.581 ± 0.248 s, right: 0.545 ± 0.244 s) [23], and Division 1 (0.49 ± 0.16 s) and 2 (0.72 ± 0.18 s) female soccer players [32] using the same assessment (10-m 505). In most cases, sex or sport differences were observed for COD performance and 10-m sprint times (Table 2, Table 3 and Table S1), with males displaying faster 10-m sprint times compared to females of the same sport (Table S1).…”
Section: Discussionmentioning
confidence: 92%
“…Despite the recent popularity of the COD deficit [21,23,32,33], to the best of our knowledge, only one study has explored asymmetries in COD deficit during the 505 and this was limited to youth female netballers [24]. Further understanding of COD ability and asymmetries in athletes from different athletic populations is needed to improve a coach’s ability to prescribe and monitor training for their athletes [34].…”
Section: Introductionmentioning
confidence: 99%